1998
DOI: 10.1152/ajpgi.1998.275.4.g705
|View full text |Cite
|
Sign up to set email alerts
|

Src kinase and PI 3-kinase as a transduction pathway in ceramide-induced contraction of colonic smooth muscle

Abstract: Ceramide mediates sustained contraction of smooth muscle cells. C2 ceramide induced a rapid increase in Src kinase activity within 15 s, peaked at 1 min, and was sustained up to 8 min. Contraction and Src kinase activity were inhibited in cells incubated in Ca2+-free medium containing 2 mM EGTA and in cells preincubated with herbimycin A, a Src kinase inhibitor. Immunoblotting using a phosphospecific anti-Src (416Y) antibody showed a ceramide-induced increase in pp60 src tyrosine phosphorylation. Immunoprecip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 17 publications
6
52
0
Order By: Relevance
“…This is not the first study to show that ceramide can activate PI 3-kinase and Akt. Human colonic smooth muscle cells have been shown to have PI 3-kinase activation downstream of ceramide (72,82). The other significant study demonstrating ceramide activation of PI 3-kinase is that by Hanna and Brindley (54), demonstrating that TNF-induced ceramide in fibroblasts activated PI 3-kinase via tyrosine kinase activity and p21…”
Section: Figurementioning
confidence: 99%
“…This is not the first study to show that ceramide can activate PI 3-kinase and Akt. Human colonic smooth muscle cells have been shown to have PI 3-kinase activation downstream of ceramide (72,82). The other significant study demonstrating ceramide activation of PI 3-kinase is that by Hanna and Brindley (54), demonstrating that TNF-induced ceramide in fibroblasts activated PI 3-kinase via tyrosine kinase activity and p21…”
Section: Figurementioning
confidence: 99%
“…Given the facts that agents that activate the PI 3-kinase/Akt1 pathway trigger an anti-apoptotic signal (59) and that ceramide regulates phospholipase D and PKC (12,60,61) and leads to activation of apoptotic signaling, it is conceivable that TNF-␣ and/or ceramide could inhibit PKC␣ through regulation of phosphoinositide-dependent kinase-1. In fact, several recent studies have reported that TNF-␣ and/or ceramide activates PI 3-kinase (62,63), whereas Zundel and Giaccia (64) have shown the inhibition of PI 3-kinase/Akt kinase by ceramide. A few other studies have demonstrated the inhibition of Akt kinase activity by ceramide, but the effect of ceramide on PI 3-kinase activity was not significant (65,66).…”
Section: Functional Dichotomy Of Pkc In Tnf-␣ Signal Transductionmentioning
confidence: 99%
“…23 Therefore, the effects of short-chain ceramides are mainly direct rather than involving metabolism to sphingosine or sphingosine 1-phosphate. 23,24 TNFa and ceramides stimulate PI 3-K in 3T3 L1 adipocytes, 22,25 fibroblasts, 23,24 smooth muscle cells, 26 osteoclasts 45 and macrophages. 46 These increases in PI 3-K are associated with protection from apoptosis and increased division rather than cell death.…”
Section: Discussionmentioning
confidence: 99%
“…22 Our later studies with Rat2 fibroblasts demonstrate that TNFa, sphingomyelinase and C 2 -ceramide rapidly stimulate tyrosine kinases, production of Ras-GTP and its association with activated PI 3-K. 23,24 Furthermore, incubation of 3T3-L1 adipocytes with TNFa increases the tyrosine phosphorylation of IRS-1 and its binding to PI 3-K. 25 Ceramides also activate Src and PI 3-K in smooth muscle cells. 26 In L6 myocytes, ceramides inhibit insulin-stimulated glucose uptake, but this did not depend upon decreased IRS-1 phosphorylation, or PI 3-K activity. 27 Ceramides appear to inhibit insulin-stimulated glucose uptake downstream of PI 3-K at the level of protein kinase B (PKB).…”
Section: Introductionmentioning
confidence: 86%